Ориентация лягушки прудовой (Rana esculenta L.) - Лялюшко, Д.М. (Вестник зоологии, 1972)
Orientation of Rana esculenta L. to the maternal warer body from a distance of 150 mm was studied. Rana esculenta orientation is established to be essentially influenced by changes in a relative humidity and temperature of air as well as by season and time of a day.